Konsistensi Desain sebagai Identitas Lembaga Amil Zakat Dompet Amanah Umat - Devinnisa Jehan Siddiqa Fabtian; Aris Sutejo (Student Research Journal, 2023)
Design is the process of planning, conceptualizing, and creating an object or system with a specific purpose. It can encompass various fields, including graphic design, product design, interior design, and many more. Design involves decision-making related to structure, function, aesthetics, and user experience to achieve specific goals. Design plays a crucial role in shaping the visual identity of an entity, whether it be a company, organization, or institution. Visual identity includes elements such as logos, colors, typography, and other design elements that become distinctive and easily recognizable. Consistency in design, using these elements, forms a strong visual identity. Therefore, this article explores how design consistency in LAZDAU has successfully created instant identification, captivated audiences, and effectively conveyed the messages intended by the institution. The results of this article can provide a deeper understanding of the essential role of design in shaping the visual identity of a zakat amil institution.